(untitled) - United States Power Squadrons (Camden, Me., 2006)
The new digital Global Maritime Distress and Safety System (GMDSS) is revolutionizing emergency communications and international search-and-rescue at sea. Clearly and concisely, this one-of-a-kind guide presents what you should know about using digital marine radios for emergency assistance and enhanced safety.
Keywords: Radio in navigation,Artificial satellites in navigation,Navigation,Distress signals; Safety measures